2008
DOI: 10.1007/s11071-008-9357-z
|View full text |Cite
|
Sign up to set email alerts
|

On the Planck scale and properties of matter

Abstract: Invariant and long-lived physical properties and structures of matter are modeled by intrinsic rotations in three and four degrees of freedom. The rotations are quantized starting from the Planck scale by using a nonlinear 1/r potential and period doublinga common property of nonlinear dynamical systems. The absolute values given by the scale-independent model fit closely with observations in a wide range of scales. A comparison is made between the values calculated from the model and the properties of the bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…The cube root in (4) returns the 3D periodic volume of the electron-positron pair to a characteristic period, which is the observable rest energy in this case [11]. The fractional exponents of two have been discovered in an earlier analysis of the experimental data [12]. The criterion for the superstability of the n'th period is defined by a subset of periods [1]:…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cube root in (4) returns the 3D periodic volume of the electron-positron pair to a characteristic period, which is the observable rest energy in this case [11]. The fractional exponents of two have been discovered in an earlier analysis of the experimental data [12]. The criterion for the superstability of the n'th period is defined by a subset of periods [1]:…”
Section: Methodsmentioning
confidence: 99%
“…The period doubling phenomenon has been observed in various physical and chemical systems like lasers [2], plasmas [3], chemical reactions [4], planetary systems [5], stars [6], and galaxy redshifts [7]. It has also been shown that electron physical properties (mass, value of the elementary charge and magnetic moment), as well as the value of the fine structure constant, can be calculated from the corresponding Planck units by the period doubling phenomenon [8,9,10,11] including the internal degrees of freedom in the system [10,12].…”
Section: Introductionmentioning
confidence: 99%
“…One method of deriving the MKS equivalent of the electromagnetic units requires formulas for Planck charge [4,8,15,16] and Planck inductance [16] q P = I P t P = 4蟺 0 c.…”
Section: Electromagnetismmentioning
confidence: 99%
“…More than a century later, the system of derived Planck units-featuring enigmatic ratios of the same three constantshas expanded deeper into the fields of quantum mechanics, thermodynamics, electromagnetism, and gravity [4][5][6][7][8][9]. Despite sharing the same building blocks, these formulas offer little insight into the physical meaning of and G, or the Planck units they are used to define.…”
Section: Introductionmentioning
confidence: 99%
“…More than a century later, the system of derived Planck units-featuring enigmatic ratios of the same three constants-has expanded deeper into the fields of quantum mechanics, thermodynamics, electromagnetism, and gravity [4][5][6][7][8][9]. Despite sharing the same building blocks, these formulas offer little insight into the physical meaning of and G, or the Planck units they define.…”
Section: Introductionmentioning
confidence: 99%